DO ANTI-SMOKING ADVERTISEMENTS INFLUENCE STUDENTS TO QUIT SMOKING? - Debri Rizki Faisal; Tati Suryati (Universitas Airlangga, 2023)
Background: The prevalence of adolescent smoking in Indonesia increased from 2013 to 2018. Aims: This study examines the influence of pro and anti-cigarette advertising on students' smoking cessation. Methods: The study uses the Global Youth Tobacco Survey Indonesia 2019 data. The sample was students aged 13-15 years who had smoked. The dependent variable is quitting smoking, and the independent variables are pro-cigarette and anti-smoking ads: chi-square and logistic regression tests with a 95% confidence interval and a p-value of 0.05. Results: The total sample was 1023 students, and 79.32% wanted to quit smoking. In the anti-smoking ads variables: anti-smoking messages in various media (OR=1.63, 95% CI=1.14-2.34); pictorial health warnings (PHW) on cigarette packs (OR=3.46, 95% CI=2.40-4.97); feeling afraid when seeing health warnings on packaged cigarettes (OR=3.03, 95% CI=2.16-4.26); education about harmful of cigarette consumption (OR=1.40, 95% CI=1.00 – 1.96) had a significant association to quit smoking. The most dominant factor in multivariate analysis was pictorial health warnings on cigarette packs (OR=2.53, 95% CI=1.67-3.81). Conclusion: Most student smokers express a desire to quit smoking. Pictorial health warnings are significantly associated with quitting smoking among students. Keywords: cigarette ads, GYTS, pictorial health warning, students